Pengaruh Pelatihan Pemasaran terhadap Kinerja Pemasaran : (Studi Kasus UMK Binaan Lazismu Jawa Barat) - Salwa Salsabila Aulia Rahmani; Dede Kurnia; Ismail Yusup (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Marketing performance plays a central role in business growth, but in practice, many MSME players still find it difficult to achieve. This study aims to determine the effect of marketing training on marketing performance among micro and small enterprises (MSEs) under the guidance of Lazismu West Java. This study uses a quantitative method with a descriptive-verificative approach. The population in this study consists of 35 MSEs under the guidance of Lazismu West Java who have participated in marketing training, and all of them were selected as samples using a saturated sampling technique. The instrument used was a Likert scale questionnaire, and the data was analyzed using simple linear regression with the help of SPSS version 29.0. The results of this study indicate that marketing training has a significant effect on improving marketing performance. The contribution provided through this training reached 62%, indicating that most of the variation in marketing performance can be explained by the effectiveness of the training attended by business actors.